2003
DOI: 10.1007/s00466-003-0428-1
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic and scalar turbulent fluctuation in a diffusion flame of an-axisymmetric methane jet into air

Abstract: A study of turbulence/combustion interactions in a relatively large turbulent diffusion flame of an axisymmetric methane jet into air is presented. A first order k-e turbulence closure model is used along with two different models (equal scales and non-equal scales) for the submodel describing the scalar dissipation rate. The flamelet concept is used to model the turbulent combustion along with a joint mixture fraction/strain rate probability density function (PDF) for the prediction of the average parameters … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…The comparison between the computed results and experimental data showed that both RANS and DDES obtained the distribution of axial velocity, tangential velocity and temperature. Hidouri et al [23] studied turbulent diffusion flames using the first-order k-ε model, along with two different methods for the sub-model, describing the scalar dissipation rate. They showed that the use of a non-equal scale model improved the obtained numerical results.…”
Section: Introductionmentioning
confidence: 99%
“…The comparison between the computed results and experimental data showed that both RANS and DDES obtained the distribution of axial velocity, tangential velocity and temperature. Hidouri et al [23] studied turbulent diffusion flames using the first-order k-ε model, along with two different methods for the sub-model, describing the scalar dissipation rate. They showed that the use of a non-equal scale model improved the obtained numerical results.…”
Section: Introductionmentioning
confidence: 99%